Gravitational lensing in the strong field limit for Kar’s metric (2013)
Abstract. Gravitational lensing studies have been considered one of the most important applications of General Theory of Relativity. The full theory of gravitational lensing has been developed based on the scheme of the weak field approximation, which has been successfully used to explain all the physical observations. However, in the last years the scientific community has started to look this phenomenon from a different point of view: the strong field limit. The reason of studying this limit is that deviation of light rays in strong fields is one of the most promising areas where a theory of gravitation can be tested in its full form. In this work we have used the method proposed by V. Bozza to calculate the strong field limit deflection angle for a light ray passing near a scalar charged spherically symmetric object described by the metric proposed by Sayan Kar. This metric came from the low-energy limit of heterotic string theory equations of motion. Using Bozza’s method, we solved the lens equation to calculate the parameters of the strong field limit expansion which are directly connected with observables such as the magnification of the images.